Four-armed Parvati performing penance - Temples of India Project Team (Jio Institute, 2024)
Inside the sanctum of the temple, beautiful sculptures of nayikas (female dancers) adorn the walls. Placed at the centre of the principal/back wall, a colossal image of Parvati in penance or the panchagni tapa. Interestingly, their names are scribed in the 10th century CE Kutila script. The inscribed epithet calls her vikata, a possible explanation for this unusual name would be Gauri treading the vikata-marga by performing penance. The unusual epithet, Vikata, also appears in the Harsha stone inscription of the 11th century CE (VS 1030). Shiva, occupying a central place in the sanctum in the form of linga placed on yoni, is accompanied by the representation of Shakti on the surrounding walls inside the sanctum itself. The four-armed Parvati is performing the penance of the panchagni tapa, visually depicted with fires on either side. She stands erect on an iguana and is hence labelled as Godhasana Gauri. On either side of her are two standing and two sitting female attendants.